Addendum to a theoretical and experimental study of the boundary layer flow on a 45 degrees swept back wing - Walton, J. (College of Aeronautics, Cranfield, 1957)
COA report 109 describes Flight Tests carried out on a swept back half wing of double elliptical section to investigate the nature of the boundary layer flow, with particular reference to Bounday Layer Instability and subsequent transition.